2009
DOI: 10.1515/jpm.2009.037
|View full text |Cite
|
Sign up to set email alerts
|

Developmental alterations of the prefrontal cerebral cortex in sudden unexplained perinatal and infant deaths

Abstract: The aim of this study was to investigate the developmental patterns of the human prefrontal cortex involved in breathing control in a wide cohort of fetal and infant death victims, aged from the 22(nd) gestational week to 10 months of life, and to evaluate whether morpho-functional disorders are present in this specific cortical area in victims of sudden unexplained death. A further aim was to determine whether prenatal absorption of nicotine could also affect the maturational processes of the prefrontal corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…It is in agreement with previous studies [1,15,16] that identify the brainstem as the primary site of dysfunction in SIDS and provides a means to understand why these infant deaths almost exclusively occur during sleep in children who show no signs of cardiac or respiratory distress during wakefulness. Furthermore, this model implicates a clear mechanism by which pacifier use could be preventative for SIDS.…”
Section: Resultssupporting
confidence: 91%
“…It is in agreement with previous studies [1,15,16] that identify the brainstem as the primary site of dysfunction in SIDS and provides a means to understand why these infant deaths almost exclusively occur during sleep in children who show no signs of cardiac or respiratory distress during wakefulness. Furthermore, this model implicates a clear mechanism by which pacifier use could be preventative for SIDS.…”
Section: Resultssupporting
confidence: 91%
“…Decreased HRV is associated with sudden death [12,44]. In a postmortem study by Lavezzi et al found developmental alterations of the prefrontal cerebral cortex in 33% of the victims of sudden infant death [24]. Moreover, Lucet et al found vagal over-activity in the family members of sudden infant death victims [27].…”
Section: Discussionmentioning
confidence: 99%
“…An altered GABAergic signalling could result in altered synaptic organization and aberrant synaptic plasticity. These detrimental eff ects may contribute to some of the clinically characterized defi cits that result from maternal smoking, such as sudden infant death syndrome and auditory cognitive dysfunction in animal models [14,35,37,53,134] as well as in humans [34,74] . Not only prenatal neurotoxic eff ects lead to damage of developing neurons.…”
Section: And Developing Neuronsmentioning
confidence: 99%